Novel 1,3,4-Oxadiazole Derivatives of Pyrrolo[3,4-d]Pyridazinone Exert Anti-Inflammatory Activity without Acute Gastrotoxicity in the Carrageenan-Induced Rat Paw Edema Test - Szandruk-Bender M; Merwid-Ląd A; Wiatrak B; Danielewski M; Dzimira S; Szkudlarek D; Szczukowski Ł; Świątek P; Szeląg A (Dove Medical Press, 2021)
Marta Szandruk-Bender,1 Anna Merwid-Ląd,1 Benita Wiatrak,1 Maciej Danielewski,1 Stanisław Dzimira,2 Danuta Szkudlarek,3 Łukasz Szczukowski,4 Piotr Świątek,4 Adam Szeląg1 1Department of Pharmacology, Wroclaw Medical University, Wrocław, Poland; 2Department of Pathology, Wroclaw University of Environmental and Life Sciences, Wrocław, Poland; 3Foundation of the Wroclaw Medical University, Wroclaw Medical University, Wrocław, Poland; 4Department of Chemistry of Drugs, Wroclaw Medical University, Wrocław, PolandCorrespondence: Marta Szandruk-BenderDepartment of Pharmacology, Wroclaw Medical University, Mikulicza-Radeckiego 2, Wrocław, 50-345, PolandTel +48717841438Fax +48717840094Email marta.szandruk@umed.wroc.plBackground and Purpose: Due to the risk of gastrointestinal damage and various tissue toxicity associated with non-steroidal anti-inflammatory drugs (NSAIDs) use, investigating new anti-inflammatory agents with efficacy comparable to that of NSAIDs but reduced toxicity is still a major challenge and a clinical need. Based on our previous study, new 1,3,4-oxadiazole derivatives of pyrrolo[3,4-d]pyridazinone, especially 6-butyl-3,5,7-trimethyl-1-[[4-[[4-(4-nitrophenyl)piperazin-1-yl]methyl]-5-thioxo-1,3,4-oxadiazol-2-yl]methoxy]pyrrolo[3,4-d]pyridazin-4-one and 6-butyl-1-[[4-[[4-(4-chlorophenyl)-4-hydroxy-1-piperidyl]methyl]-2-thioxo-1,3,4-oxadiazol-5-yl]methoxy]-3,5,7-trimethyl-pyrrolo[3,4-d]pyridazin-4-one (hereafter referred to as the compounds 10b and 13b, respectively) seem to be promising anti-inflammatory agents. This study aimed to elucidate the effects of these two new derivatives on the course of experimental rat inflammation, liver and kidney function, and gastric mucosa.Methods: The anti-inflammatory effect of compounds 10b and 13b was evaluated using the carrageenan-induced paw edema test in rats. The increase in paw volume (paw edema), prostaglandin E2 (PGE2), tumor necrosis factor-α (TNF-α) and myeloperoxidase (MPO) levels, histological alterations, and inflammatory cell infiltration in paw tissue were determined. Serum alanine transaminase (ALT) and aspartate transaminase (AST) activities, serum urea and creatinine levels, as well as changes in gastric mucosa, were measured as indicators of hepatic, renal, and gastric toxicity.Results: Pretreatment with both novel derivatives at 10 mg/kg and 20 mg/kg doses reduced paw edema, counteracted the increased PGE2 and TNF-α levels, reduced the influx of inflammatory cells, and decreased histopathological alterations in paw tissue. Compound 13b at a dose of 20 mg/kg was more effective than indomethacin in reversing the increased TNF-α levels and reducing the influx of inflammatory cells. Only compound 13b at all studied doses (5, 10, or 20 mg/kg) counteracted the increased MPO level in paw tissue. Both compounds neither caused alterations in ALT, AST, urea, creatinine parameters nor gastric mucosal lesions.Conclusion: New compounds exert an anti-inflammatory effect, presumably via inhibiting inflammatory mediators release and inflammatory cell infiltration. Moreover, both possess a more favorable benefit-risk profile than indomethacin, especially compound 13b.Keywords: carrageenan, anti-inflammatory agents, pyrrolo[3,4-d]pyridazinone, 1,3,4-oxadiazole, inflammatory mediators, toxicity